1975
DOI: 10.1097/00004032-197503000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological Aspects and Radiation Levels Associated With the Milling of Monazite Sand

Abstract: One of the chief problems in industrial radiological health in Brazil concerns 420 people in a plant processing monazite sand, a rare earth mineral containing up to 6 per cent Tho, and 0.3 per cent U,08.Radiation hazards associated with ore concentration and chemical treatment were assessed by sampling and measurement of airborne radioactivity, 210Po bioassay in urine and chromosomal analysis in peripheral blood lymphocytes collected from plant personnel.Results showed that 2lzPb (t1/2 = 10.64 hr) airborne con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…One particular difficulty when using miner cohorts can be ascribing any observed biological effects to a particular exposure, as mining environments are known to contain a number of toxic agents (e.g., arsenic, lead and silica). Despite this limitation, a number of reports have identified an increase in CA frequencies among miners exposed to high radon concentrations, in addition to studies investigating uranium [159] or plutonium [160] compounds.…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One particular difficulty when using miner cohorts can be ascribing any observed biological effects to a particular exposure, as mining environments are known to contain a number of toxic agents (e.g., arsenic, lead and silica). Despite this limitation, a number of reports have identified an increase in CA frequencies among miners exposed to high radon concentrations, in addition to studies investigating uranium [159] or plutonium [160] compounds.…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…A continuation of the Costa-Ribeiro et al [159] study investigated 202 subjects from a Brazilian population environmentally exposed to high background radiation concentrations [173]. An increase of chromosome breaks was identified in blood lymphocytes of subjects who had a local residency of at least eight-years when compared to a control group of 147 individuals from a region of similar socio-economic status but with normal background levels of radiation.…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…The first epidemiologic studies reported in the literature evaluated the relation between measured radon exposures and cytogenetic markers (primarily structural changes in chromosomes) in peripheral lymphocytes [Kilibarda et al, 1969;Barcinski et al, 1975;Costa-Ribeiro et al, 1975;Brandom et al, 1978;Pohl-Ruling and Fischer, 1979]. Though a number of these studies reported increases related to radon exposures, the results were not adjusted for confounding variables, influential data points, and outliers; moreover, the radon doses may have been inaccurate.…”
Section: Additional Epidemiologic Evidencementioning
confidence: 99%
“…The sole published report is that of Costa-Ribeiro et al (Co75) who studied a population of Brazilian workers from a monazite processing mill. The sole published report is that of Costa-Ribeiro et al (Co75) who studied a population of Brazilian workers from a monazite processing mill.…”
Section: Introductionmentioning
confidence: 99%